Mini-Invasive Bentall Procedure Performed via a Right Anterior Thoracotomy Approach With a Costochondral Cartilage Sparing - Ji, Qiang; Wang, YuLin; Liu, FangYu; Yang, Ye; Li, Jun; Sun, XiaoNing; Yang, ZhaoHua; Pan, Sun; Lai, Hao; Wang, ChunSheng (Frontiers in Cardiovascular Medicine, 2022)
Objectives: A right minithoracotomy approach with a sternal sparing technique is a minimally invasive option for surgeons performing aortic root surgery. This report presents our initial clinical results of the right minithoracotomy Bentall procedure. Methods: Clinical data of 15 patients were retrospectively analyzed who underwent the minimally invasive Bentall procedure through the right anterior thoracotomy via the second intercostal incision without any costochondral cartilage invasion at our institution between October, 2019 and June, 2021. The operative time, length of intensive care unit stay and postoperative hospital stay, perioperative outcomes, and follow-up results were analyzed. Results: The median aortic cross-clamping time was 95.0 (85.5-98.8) min. Three (21.4%) patients received blood transfusion. The median drainage volume in the first 24 hours was 200.0 ml, with no redo for bleeding. The median duration of mechanical ventilation was 12.5 (11.0-25.0) hours, and median length of intensive care unit stay was 1.5 (1.0-3.0) day. All patients discharged 5.8±1.2 days following surgery, with no dead patients found. At 6 months following surgery, all patients survived with an improved New York Heart Association (NYHA) functional class. Conclusions: The right minithoracotomy Bentall procedure may be performed safely with low morbidity and mortality. This approach should be considered as an option in carefully selected patients requiring aortic root replacement.